FocECM33, a GPI-anchored protein, regulates vegetative growth and virulence in Fusarium oxysporum f. sp. cubense tropical race 4. Issue 3 (March 2022) - Huang, Huoqing; Zhang, Xiaoxia; Zhang, Yong; Yi, Ganjun; Xie, Jianghui; Viljoen, Altus; Wang, Wei; Mostert, Diane; Fu, Gang; Peng, Changcao; Xiang, Dandan; Li, Chunyu; et al.
Abstract: ECM33, a glycosylphosphatidylinositol (GPI)-anchored protein, is important for fungal development and infection through regulating fungal cell wall integrity, however, the functions of its orthologs in pathogenesis have not been characterized in Fusarium oxysporum . Here, we discovered a GPI-anchored protein, FocECM33, which is required for vegetative growth and virulence of Fusasium oxysporum f. sp. cubense tropical race 4 ( Foc TR4). FocECM33 was highly upregulated during the early infection process of Foc TR4 in banana roots. The targeted disruption of FocECM33 led to decreased hyphal growth, increased sensitivity to cell wall stresses and reduced virulence on banana plantlets. Furthermore, Δ FocECM33 mutant demonstrated a cell morphology defect, elevated ROS production and increased chitin content. Transcriptome analysis showed that FocECM3 3 has a significant influence on the production of various secondary metabolites and regulation of many biosynthetic processes in Foc TR4. Taken together, it seems FocECM33 contributes to the virulence of Foc TR4 through regulating the process of hyphal growth, ROS production and chitin synthesis.